PENGARUH MENGGAMBAR TERHADAP KEMAMPUAN MENULIS ANAK USIA 5-6 TAHUN - Nina Ramadhanti; Luluk Asmawati; Kristiana Maryani (STKIP Subang, 2023)
Writing is a complex activity that requires a well-coordinated interaction of motor and visual skills. Writing skills are process and result skills. So it is difficult for early childhood to master because writing is not owned by children, it must go through processes and stimuli that take a long time for children to produce writing. Children aged 4 to 6 need to practice their fine motor skills to develop their writing skills. This study aims to determine the effect of drawing on the writing ability of children aged 5-6 years. This research uses quantitative methods (quasi experiment) with Nonequivalent Control Group Design. This study used two samples, experimental group and control group, each consisting of 12 children aged 5-6 years, and given different treatment. Based on the results of data analysis using SPSS Statistics version 25 with the t-test in the form of a paired sample t-test in the experimental group it is known that the Sig. (2-tailed) is 0.000 < 0.05, so there is a significant effect, thus Ho is rejected and Hi is accepted. Further, change after treatment from the experimental group in the pretest to the posttest up by 12.17, while in the control group the change from pretest to posttest increased by 7.86, are known that the biggest change was in the experimental group with drawing treatment on children's writing abilities. It can be concluded that there is an influence of drawing on early childhood writing abilities.